Value of Manchester Acute Coronary Syndromes Decision Rule in the Detection of Acute Coronary Syndrome; a Systematic Review and Meta-Analysis - Ramezani, Fatemeh; Ahmadi, Sajjad; Faridaalaee, Gholamreza; Baratloo, Alireza; Yousefifard, Mahmoud (Archives of Academic Emergency Medicine, 2018)
Introduction: There is still no consensus on the value of Manchester Acute Coronary Syndromes (MACS) decision rule in detecting acute coronary syndrome (ACS). Therefore, the purpose of the present systematic review and meta-analyzes is to summarize the clinical evidence in the evaluation of the value of MACS in the diagnosis of ACS. Methods: A literature search was performed on the Medline, Embase, Scopus, and Web of Science databases. Outcomes included acute myocardial infarction (AMI) and major adverse cardiac event (MACE). Data were analyzed in the STATA 14.0 statistical program and the results were reported as summary receiver operating characteristics (SROC), sensitivity, specificity, positive and negative likelihood ratio, and diagnostic odds ratio with 95% confidence interval (95% CI). Results: Finally, 8 articles included in the meta-analysis. The area under the SROC of MACS was excellent in rule out of AMI (AUC = 0.99, 95% CI: 0.97 to 0.99) and MACE (AUC = 0.97, 95% CI: 0.95 to 0.98). The sensitivity and specificity of the troponin-only MACS/history electrocardiogram alone MACS (HE-MACS) in the rule out of AMI were0.99 (95% CI: 0.98-0.99) and 0.22 (95% CI: 0.11-0.37), respectively, and for the original MACS were in order 0.99 (95% CI: 0.98-0.99) and 0.26 (95% CI: 0.20-0.34),. The sensitivity and specificity of the troponin-only MACS / HE-MACS in the rule out of MACE were 0.94 (95% CI: 0.92-0.96) and 0.22 (95% CI: 0.12-0.39) compared to the 0.99 (95% CI: 0.98-0.99) and 0.27 (95% CI: 0.22-0.33) for the original MACS. Conclusion: The findings of this study showed that original MACS, troponin-only MACS, and HE-MACS are able to rule out AMI and MACE. However, further studies are needed in developing countries to confirm its external validity.